(untitled) (Scientiae Studia, 2012)
The aim of this work is to discuss "Darwinism: its past, its present, its future", a lecture given in 1875 by Miranda Azevedo as one of the "Popular Lectures of the Gloria Neighborhood, Rio de Janeiro". In this lecture Azevedo elaborates the concepts of evolution, human evolution, progress and the idea of man as the pinnacle of evolution and the master of the selective laws governing nature. We will analyze the article, published in 1876, that contains the full text of Azevedo's lecture. Of particular importance is his affiliation to Haeckel, something already commented on in Brazilian historiography. But, unlike other studies devoted to the theme, I will examine in detail Azevedo's text, attempting to show how he relates hereditary and selective evolutionary processes to thinking about how future Brazilian generations could progress.